Goa Development Report - Planning Commission (Planning Commission, 2011)
This Goa State Development Report documents: issues and their fiscal implications, the institutions and governance, the infrastructure, the development and growth areas, the carrying capacity and sustainable activity, the strengths, weakness, opportunities and threats, the outlook: possible scenarios in the short, medium and long term and recommendations and development strategies for different sectors of the Goa economy.
Planning Commission Government of India
Planning Commission Government of India